Freedom to roam: a Deleuzian overture for the concept of care in nursing - Drummond, John (Nursing philosophy, 2002)
From a position informed by the philosophical legacy of Gilles Deleuze and Felix Guattari, this paper examines the idea of ‘care’ in nursing theory and philosophy. Deleuze and Guattari make a distinction between, on the one hand, ‘concepts’, which are the proper domain of philosophy and, on the other, ‘functives’ which are the domain of science and all other empirical matters. At first blush, this distinction and use of the word concept appears rather odd, but Deleuze and Guattari hold it to be important for reasons that go beyond the acknowledged and obvious differences between philosophy and science. In Deleuzian terms, a ‘functive’ is any proposition that makes a verifiable truth-claim about actual states of affairs, whereas a ‘concept’ is a philosophical tool that, although it is used in statements that make claims and that seek to affect our thinking on states of affairs, is not a representation of them in any verifiable (functive) sense. In this respect, philosophical concepts, and the statements in which they are used, are neither true nor false. I argue that the way in which the word ‘care’ is used in much nursing theory and philosophy conflates concept (neither true nor false) with functive (either true or false) with less than productive results. I seek to persuade that if we can gain more clarity between the use of care as a would-be functive and its use as a philosophical concept, this would strengthen the purpose of the use of the idea of care in nursing theory. This is to say that I take the view that the role of ‘care’ as a philosophical concept is to be used in statements that ‘think the event’ called nursing; that seek to be ‘worthy of the event’, but without being an actual part of the event. Finally, I show how the concept of care in nursing philosophy has been, and can continue to be, reworked to achieve the permanent task of surveying the ever-shifting planes of the event and how it is described.